Following the terrestrial tracks of Caulobacter - redefining the ecology of a reputed aquatic oligotroph. Issue 12 (December 2018) - Wilhelm, Roland
Abstract For the past 60 yearsCaulobacter spp . have been commonly attributed an aquatic and oligotrophic lifestyle yet are not uncommon in nutrient-rich or soil environments. This study evaluates the environmental and ecological associations ofCaulobacter to reconcile past evidence, largely limited to culturing and microscopy, with currently available metagenomic and genomic data. The distribution ofCaulobacter species and their characteristic adhesion-conferring genes, holdfast (hfaAB ), were determined using collections of 10, 641 16S rRNA gene libraries (196 studies) and 2625 shotgun metagenomes (190 studies) from a range of terrestrial and aquatic environments. Evidence for ecotypic variation was tested in 26 genomes sourced from soil, rhizosphere, plant, groundwater, and water.Caulobacter were, on average, fourfold more relatively abundant in soil than in aquatic environments, and abundant in decomposing wood, compost, and particulate matter (in air and water).Caulobacter holdfast genes were 35-fold more abundant in soils than aquatic environments. Ecotypic differences between soil and aquaticCaulobacter were evident in the environmental associations of several species and differences in genome size and content among isolates. However, most abundant species were common to both environments, suggesting populations exist in a continuum that was evident in the re-analysis of studies on the temporal dynamics of, and sources of bacterioplankton to, lakes and rivers. This study provides a new perspective on the ecological profile ofCaulobacter, demonstrating that members of this genus are predominantly soil-borne, possess an overlooked role in plant matter decomposition and a dependency on water-mediated dispersal.